2019
DOI: 10.1007/s40279-019-01087-9
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Crossover Studies Comparing Physiological, Perceptual and Performance Measures Between Treadmill and Overground Running

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 47 publications
(158 reference statements)
2
50
2
Order By: Relevance
“…The absence of air resistance in MT running reduces oxygen uptake and theoretically improves MT performance compared to overground running. In addition to a lack of comfort and lack of sweat evaporation and hence thermoregulation that can explain these differences [30], the findings of the current review suggest that biomechanical differences may also contribute to a higher energy cost and hence reduced running performance during MT compared to overground running. Specifically, numerous studies have found that modifications of running technique acutely decrease running economy [96][97][98][99].…”
Section: Implications For Training Research and Clinical Practicementioning
confidence: 85%
See 3 more Smart Citations
“…The absence of air resistance in MT running reduces oxygen uptake and theoretically improves MT performance compared to overground running. In addition to a lack of comfort and lack of sweat evaporation and hence thermoregulation that can explain these differences [30], the findings of the current review suggest that biomechanical differences may also contribute to a higher energy cost and hence reduced running performance during MT compared to overground running. Specifically, numerous studies have found that modifications of running technique acutely decrease running economy [96][97][98][99].…”
Section: Implications For Training Research and Clinical Practicementioning
confidence: 85%
“…MT running may therefore be suitable for rehabilitation from lower limb stress fractures, but not Achilles tendinopathy, Achilles ruptures or calf muscle strains. Finally, our previous systematic review found reduced endurance performance and no significant difference in oxygen uptake between non-inclined MT and overground running at speeds < 18 km/h [30]. The absence of air resistance in MT running reduces oxygen uptake and theoretically improves MT performance compared to overground running.…”
Section: Implications For Training Research and Clinical Practicementioning
confidence: 86%
See 2 more Smart Citations
“…Of note, field running testing could be more difficult to apply due to the constraints associated with field and weather conditions. However, field testing may present greater validity for training prescriptions when compared to laboratory-based testing on a treadmill [63]. Therefore, runners and coaches should identify the tests that better suit the needs and possibilities for monitoring targeted physiological adaptations to training over the season for specific objectives.…”
Section: Training Monitoringmentioning
confidence: 99%